DISCOSIPHONELLA MINIMA SENOWBARI-DARYAN & LINK AND SOLENOLMIA? PARVA N. SP. ("SPHINCTOZOA", PORIFERA) FROM THE UPPER TRIASSIC (NORIAN) OF THE SOUTHERN APPENNINES (NORTHERN CALABRIA/ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
Two hypercalcified sphinctozoan sponges are described from several localities of dolomitic Norian reefs of northern Calabria (southern Italy). Solenolmia? parva n. sp. occurs as an extremely abundant, albeit local, component in peculiar bioconstructions dominated by serpulids and microbialitic crusts. Discosiphonella minima Senowbari-Daryan & Link, previously recognized only in the type locality of Turkey, has been now found also as a minor component in association with other typical "Dachstein" reef biota, such as corals, sponges, microbial crusts and fragments of "microproblematica". Solenolmia? parva assemblage represents the primary framebuilder of small build-ups which developed on the margins of restricted intraplatform basins. The Discosiphonella minima assemblages were found as resedimented blocks along the slope of intraplatform anoxic basins. The distribution of the different reefal assemblages of Northern Calabria can be related to the paleogeographic position of northern Calabria with respect to the evolution of Triassic crustal extension in western Mediterranean.
Keywords: Sponge; “Sphinctozoa”; Solenolmia; Norian; Southern Appennines; Northern Calabria; Italy; Paleogeography